Legal Analysis of Drug Traffickers Based on: Analysis of Supreme Court Decision Number 5832 K/Pid.Sus/2022 - Gita Suci Pratiwi; T. Riza Zarzani; Rahmayanti Rahmayanti (International Journal of Law and Society, 2024)
The 2009 Narcotics Law, also known as Law 35, demonstrates a clear intention to deter people from committing drug-related offences. To achieve this, the law applies stricter penalties, including the possibility of the death penalty, with minimum and maximum sentences set based on the severity of the threat posed by drug abuse and illicit trafficking. These measures are crucial in maintaining national security and safeguarding the resilience of our society. This research consists of a legal review of the criminal offence of drug trafficking and the eradication of drug trafficking in Indonesia. This includes an analysis of Supreme Court Decision Number 5832 K/Pid.Sus/2022. The research methodology used is normative legal research, with a descriptive approach. The data for this research is collected from primary and secondary sources through the literature research method. The death penalty is expressly mentioned as an appropriate punishment for serious drug offenders in Law Number 35 Year 2009 on Narcotics. The implementation of this punishment in Indonesia is essential to protect the state, society, and public interest. The act of trafficking narcotics poses a great threat to these three interests so it is justifiable to impose the death penalty on the perpetrators. In line with Supreme Court Decision Number 5832 K/Pid.Sus/2022, the author agrees with the decision of the panel of judges who revoked the defendant's acquittal and imposed the death penalty. This decision is very appropriate for drug dealers who continue to carry out illegal activities even though they have been imprisoned.